Catholic inculturation in Vietnam, the Philippines, and South Korea: a comparative study - Tran, Quang Vu (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2025)
In the context of globalisation and the growing interplay between religion, politics, and culture, the inculturation of Catholicism in Asia presents a significant case for examining how universal faith traditions adapt within diverse socio-political environments. This study addresses two main problems, namely, (a) what forms of Catholic inculturation have emerged in Vietnam, the Philippines, and South Korea, and (b) how cultural traditions, historical trajectories, and political frameworks shape these processes. Adopting a comparative case-study approach, the research employs thematic content analysis of triangulated secondary sources, including scholarly literature, official state and Church documents, and institutional reports, within a theoretical framework that conceptualises inculturation as a dialogue between the Gospel and local culture. The findings identify three distinctive models: (a) the Philippines demonstrates ‘comprehensive integration’, where Catholicism is deeply embedded in national identity; (b) South Korea illustrates ‘contestation and adaptation’, where Catholic identity was forged through persecution, conflict, and socio-political activism; and (c) Vietnam reflects ‘adaptation within boundaries’, where Catholicism develops under a socialist legal framework while aligning with cultural and national principles. By highlighting the salient influence of political authority and historical pathways, this study contributes a refined comparative framework for understanding Catholic inculturation in Asia, moving beyond purely cultural explanations to show how contextualisation can operate as cultural integration, a socio-political force, or a state-accommodated (socialist-oriented) form of adaptation.